Lymphoid Blast Crisis in a Case of Paediatric Chronic Myeloid Leukaemia: An Unusual Presentation of an Uncommon Malignancy - Balraam, K V Vinu; Somasundaram, Venkatesan; Garg, Nidhi; Sharma, Sanjeevan; K S, Sampath; Bharadwaj, Reena (Annals of Pathology and Laboratory Medicine, 2018)
Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm in which the granulocytes are the major proliferative component and is characterised by the chromosomal translocation t(9;22)(q34.1;q11.2) leading to the formation of Philadelphia chromosome (Ph) containing the BCR-ABL1 fusion gene. This entity is quite rare in paediatric age group and even unusual is a child presenting for the first time in an accelerated or blast crisis. Here we unfold an noteworthy case of a 9 year old school going child presenting with complains of vague abdominal distension who on further evaluation was found to be living through leukaemia.